Solder paste

By adjusting the flow characteristics and composition of the solder paste, the problem of unstable solder paste dispensing in the dispensing method was solved, achieving stable supply and uniform coating of solder paste and reducing the phenomenon of blank soldering.

CN119497659APending Publication Date: 2025-02-21MITSUBISHI MATERIALS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380052083.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the dispensing method, the amount of solder paste dispensed is unstable, which can easily lead to the problem of incomplete soldering.

Method used

By controlling the flow characteristics of the solder paste, especially adjusting the loss tangent tanδ to a range of 0.1 or higher and 0.5 or lower, and controlling the viscosity to a range of 50 Pa·s or higher and 100 Pa·s under conditions of 25°C and a shear rate of 6/s, a solder paste combination containing metal powder, resin, solvent and thixotropic agent is used to optimize the length of the linear viscoelastic region for stable dispensing.

Benefits of technology

It achieves stable supply and application of solder paste in the dispensing method, reduces the phenomenon of open solder joints, and improves the uniformity and stability of coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497659A_ABST
    Figure CN119497659A_ABST
Patent Text Reader

Abstract

The solder paste contains a metal powder, a resin, a solvent, and a thixotropic agent, and has a loss tangent in the range of 0.1-0.5 when the strain is 0.01%. The length of the linear viscoelastic region defined by the range of shear stress corresponding to the strain region in which the loss tangent is from N0 to 1.1 * N0 is preferably less than 12 Pa, where N0 is the loss tangent when the strain is 0.01%. It is preferable that the viscosity measured under the conditions of a temperature of 25 DEG C and a shear rate of 6 / s is within the range of 50 Pa.s to 100 Pa.s (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solder paste used when soldering a first component and a second component.

[0002] This application incorporates the contents of patent application No. 2021-200809 filed in Japan on December 10, 2021. Background Art

[0003] For example, semiconductor devices such as LEDs and power modules have a structure in which a semiconductor element is bonded to a circuit layer formed of a metal member.

[0004] When joining electronic components such as semiconductor elements to a circuit layer, methods using solder paste are widely used, as shown in Patent Documents 1 to 3, for example.

[0005] Here, as a method of supplying solder paste to the bonding surface, there are methods such as printing, dispensing, and pin transfer.

[0006] Patent Document 1: Japanese Patent Application Publication No. 2000-271782

[0007] Patent Document 2: Japanese Patent No. 6459656

[0008] Patent Document 3: Japanese Patent No. 6428339

[0009] However, in the dispensing method, since the solder paste is squeezed out by a cylinder, there is an advantage that the solder paste can be applied even to joint surfaces of various shapes.

[0010] However, in the dispensing method, the amount of solder paste discharged tends to become unstable, and the solder paste cannot be sufficiently discharged, which may cause so-called empty soldering. Summary of the invention

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a solder paste that can be stably supplied even when applied by a dispensing method.

[0012] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that the flow characteristics of solder paste are greatly affected by the ratio of the elasticity (storage modulus G" in dynamic viscoelasticity measurement) and viscosity (loss modulus G' in dynamic viscoelasticity measurement) of the solder paste, that is, the loss tangent tanδ=G" / G'. Therefore, by properly controlling the loss tangent, it is possible to stably discharge the solder paste from the cylinder even in the dispensing method.

[0013] The present invention has been completed based on the above findings. In one embodiment of the present invention, a solder paste includes metal powder, resin, solvent and thixotropic agent, wherein the loss tangent at a strain of 0.01% is within a range of 0.1 to 0.5.

[0014] According to the solder paste of this structure, since the loss tangent when the strain is 0.01% is greater than 0.1, the stress required when starting to dispense is reduced, and the solder paste can be stably discharged. On the other hand, since the loss tangent when the strain is 0.01% is less than 0.5, the shape of the applied solder paste can be maintained, and the solder paste can be stably applied.

[0015] Here, in the solder paste involved in one embodiment of the present invention, when the loss tangent at a strain of 0.01% is set to N0, the length of the linear viscoelastic region defined by the range of shear stress corresponding to the strain region of the loss tangent from N0 to 1.1×N0 is preferably less than 12 Pa.

[0016] At this time, since the length of the linear viscoelastic region is suppressed to less than 12 Pa, the stress required to start dispensing becomes further lower, and more stable dispensing is possible.

[0017] Furthermore, in the solder paste according to one embodiment of the present invention, the viscosity measured under the conditions of a temperature of 25° C. and a shear rate of 6 / s is preferably within a range of 50 Pa·s to 100 Pa·s.

[0018] At this time, since the viscosity measured under the conditions of a temperature of 25° C. and a shear rate of 6 / s is set in the range of 50 Pa·s or more and 100 Pa·s or less, it is possible to discharge more stably by the dispensing method.

[0019] According to the present invention, it is possible to provide a solder paste that can be stably supplied even when applied by a dispensing method. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a graph showing the measurement of dynamic viscoelasticity of the solder paste according to one embodiment of the present invention.

[0021] Figure 2 This is a graph showing the relationship between the loss tangent and strain of the solder paste of Example 3 of the present invention in the examples.

[0022] Figure 3 This is a graph showing the relationship between the loss tangent and strain of the solder paste of the comparative example in the example. DETAILED DESCRIPTION

[0023] Hereinafter, solder paste as an embodiment of the present invention will be described.

[0024] The solder paste of this embodiment is used when soldering a first member and a second member, for example, when soldering a semiconductor element (second member) as an electronic component to a circuit layer (first member) of an insulating circuit board.

[0025] The solder paste of this embodiment includes metal powder, resin, solvent, and thixotropic agent, and may also include an activator as needed.

[0026] In addition, in the solder paste of the present embodiment, in the dynamic viscoelasticity measurement, the loss tangent at a strain of 0.01% is within the range of 0.1 to 0.5. The results of the dynamic viscoelasticity measurement of the solder paste of the present embodiment are shown in FIG. Figure 1 middle.

[0027] The loss tangent is the ratio of the elasticity (storage modulus G") in the dynamic viscoelasticity measurement to the viscosity (loss modulus G' in the dynamic viscoelasticity measurement) of the paste.

[0028] Loss tangent tanδ = G" / G'

[0029] Here, when the loss tangent is less than 0.1 at a strain of 0.01%, the stress required to start dispensing becomes large, and the solder paste may not be stably discharged. On the other hand, when the loss tangent exceeds 0.5 at a strain of 0.01%, the shape of the applied solder paste cannot be maintained, and the deviation of the applied solder paste may become large.

[0030] Therefore, in the present embodiment, the loss tangent when the strain is 0.01% is set within the range of 0.1 to 0.5.

[0031] Here, the loss tangent at a strain of 0.01% is more preferably 0.2 or more, and the loss tangent at a strain of 0.01% is more preferably 0.3 or less.

[0032] Furthermore, when the equivalent circle diameter of the discharge port of the cylinder that discharges the solder paste is 1.0 mm or less, the loss tangent when the strain is 0.01% is preferably set to 0.3 or less.

[0033] Here, in the solder paste of this embodiment, when the loss tangent at a strain of 0.01% is defined as N0, the length of the linear viscoelastic region defined by the range of shear stress corresponding to the strain region of the loss tangent from N0 to 1.1×N0 is preferably less than 12 Pa.

[0034] In the solder paste of the present embodiment, by setting the length of the linear viscoelastic region to less than 12 Pa, the stress required at the start of dispensing can be further reduced, and the solder paste can be stably discharged.

[0035] Furthermore, it is further preferred that the length of the linear viscoelastic region be 10 Pa or less.

[0036] Furthermore, in the solder paste of the present embodiment, the viscosity measured under the conditions of a temperature of 25° C. and a shear rate of 6 / s is preferably within a range of 50 Pa·s to 100 Pa·s.

[0037] In the solder paste of the present embodiment, by setting the viscosity in the range of 50 Pa·s to 100 Pa·s, it can be more stably discharged by dispensing. The viscosity is more preferably in the range of 50 Pa·s to 80 Pa·s.

[0038] Examples of the metal powder contained in the solder paste of this embodiment include Sn-Ag-Cu, Au-Sn, Sn-Cu, Pb-Sn, and Au-Ge. These metal powders may be alloy powders or mixed powders. In this embodiment, the metal powder is a mixed powder of Au powder and Sn powder.

[0039] As the resin contained in the solder paste of the present embodiment, for example, polymerized rosin, natural rosin, purified rosin, isobornylcyclohexanol, rosin ester, etc. can be used.

[0040] As the solvent contained in the solder paste of the present embodiment, for example, solvents such as alcohols, ketones, esters, ethers, aromatics, hydrocarbons, terpenes, and terpenoids can be used. Specifically, benzyl alcohol, ethanol, ethanol, isopropanol, butanol, diethylene glycol, ethylene glycol, ethyl cellosolve, butyl cellosolve, butyl carbitol, isopropanol, ethyl acetate, butyl acetate, butyl benzoate, diethyl adipate, dodecane, tetradecene, α-terpineol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, toluene, xylene, propylene glycol monophenyl ether, diethylene glycol monohexyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, diisobutyl adipate, hexylene glycol, cyclohexanedimethanol, 2-terpinyloxyethanol, 2-dihydroterpinyloxyethanol, citral, linalool, limonene, carvacrol, pinene, farnesene, ethyl myristate, etc. can be used alone or in combination.

[0041] As the thixotropic agent contained in the solder paste of this embodiment, for example, solidified castor oil, hydrogenated castor oil, carnauba wax, amides, hydroxy fatty acids, dibenzylidene sorbitol, bis(p-methylbenzylidene)sorbitol, beeswax, stearic acid amide, hydroxystearic acid ethylenebisamide, etc. can be used alone or in combination.

[0042] When the solder paste of this embodiment contains an activator, as the activator, for example, fatty acids such as adipic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, hydroxy fatty acids such as 1,2-hydroxystearic acid, antioxidants, surfactants, amines, etc. can be added for use.

[0043] Here, the content of the metal powder is preferably in the range of 75 mass % or more and 95 mass % or less, and more preferably in the range of 80 mass % or more and 92 mass % or less.

[0044] The content of the resin is preferably in the range of 1.0% by mass or more and 10.0% by mass or less. The content of the resin is more preferably in the range of 4.0% by mass or more and 8.0% by mass or less.

[0045] The content of the solvent is preferably in the range of 1.0 mass % to 10.0 mass %, and more preferably in the range of 4.0 mass % to 8.0 mass %.

[0046] The content of the thixotropic agent is preferably in the range of 0.1 mass % to 2.0 mass %, and more preferably in the range of 0.1 mass % to 1.5 mass %.

[0047] The content of the activator is preferably in the range of 0 mass % to 3.0 mass %. The content of the activator is preferably in the range of 0 mass % to 2.0 mass %.

[0048] In addition, each content is a value when the solder paste is taken as 100 mass %.

[0049] When the flux including the resin, the solvent, the thixotropic agent, and the activator is taken as 100% by mass, the content of the resin is preferably 40% by mass or more.

[0050] Next, a method for producing the solder paste according to the present embodiment will be described.

[0051] First, a portion of the thixotropic agent is added to a solvent and stirred, and the solvent is heated to a temperature higher than the dissolution temperature of the thixotropic agent. Then, a resin and an activator are added and stirred to obtain a mixture. And, during the cooling of the obtained mixture, the remaining thixotropic agent is added.

[0052] For the thixotropic agent added before heating, the crystal nucleus grows during the heating process, and the grains of the thixotropic agent coarsen. On the other hand, the grains of the thixotropic agent added during cooling do not coarsen. In this way, by controlling the state of the grains of the thixotropic agent contained in the solder paste, the viscoelastic properties (loss tangent) of the solder paste can be adjusted.

[0053] Furthermore, when the total amount of the thixotropic agent used is taken as 100%, the ratio of the thixotropic agent added before heating is preferably in the range of 40% to 95%, and the ratio of the thixotropic agent added during cooling is preferably in the range of 5% to 60%.

[0054] When the total amount of the thixotropic agent used is taken as 100%, the ratio of the thixotropic agent added before heating is more preferably in the range of 50% to 80%, and the ratio of the thixotropic agent added during cooling is more preferably in the range of 20% to 50%.

[0055] When a portion of the thixotropic agent is added to the solvent and stirred and heated, it is preferably heated to a temperature 10 to 20° C. higher than the dissolution temperature of the thixotropic agent. The temperature when the remaining thixotropic agent is added is preferably 5 to 10° C. lower than the dissolution temperature of the thixotropic agent.

[0056] According to the solder paste of the present embodiment configured as above, since the loss tangent when the strain is 0.01% is 0.1 or more, the stress required when starting to dispense is reduced, and the solder paste can be stably dispensed. On the other hand, since the loss tangent when the strain is 0.01% is 0.5 or less, the shape of the applied solder paste can be maintained, and the solder paste can be stably applied.

[0057] In the solder paste of this embodiment, when the loss tangent at a strain of 0.01% is defined as N0, the length of the linear viscoelastic region defined by the range of shear stress corresponding to the strain region of the loss tangent from N0 to 1.1×N0 is preferably less than 12 Pa.

[0058] At this time, since the length of the linear viscoelastic region is suppressed to less than 12 Pa, the stress required to start dispensing becomes further lower, and more stable dispensing is possible.

[0059] Furthermore, in the solder paste of the present embodiment, the viscosity measured under the conditions of a temperature of 25° C. and a shear rate of 6 / s is preferably within a range of 50 Pa·s to 100 Pa·s.

[0060] At this time, since the viscosity measured under the conditions of a temperature of 25° C. and a shear rate of 6 / s is set in the range of 50 Pa·s or more and 100 Pa·s or less, it is possible to discharge more stably by the dispensing method.

[0061] As mentioned above, although embodiment of this invention was described, this invention is not limited to this, It can change suitably within the range which does not deviate from the technical idea of ​​this invention.

[0062] For example, in this embodiment, a case where a semiconductor element (second component) is bonded to a circuit layer (first component) of an insulating circuit board as an electronic component is described, but the present invention is not limited thereto, and the first component and the second component are not particularly limited.

[0063] In the present embodiment, in the method for manufacturing solder paste, a case is described in which a portion of a thixotropic agent is added to a solvent and stirred and heated, and then a resin and an activator are added and stirred to obtain a mixture. However, this is not limited to this, and a portion of a thixotropic agent, a resin, and an activator may be added to a solvent and then heated and stirred to obtain a mixture.

[0064] Example

[0065] Hereinafter, the results of evaluation tests for evaluating the effects of the solder paste according to the present invention will be described.

[0066] First, as shown in Table 1, a resin, a solvent, and a thixotropic agent were mixed, heated to 150° C. and stirred, and then cooled to room temperature and mixed with metal powder to prepare various solder pastes.

[0067] As shown in Table 1, the thixotropic agent was added twice: before heating and at the start of cooling after heating.

[0068] The loss tangent, the length of the linear viscoelastic region, the viscosity, and the dispensing property of each of the obtained solder pastes were evaluated as follows.

[0069] (Loss tangent and length of linear viscoelastic region)

[0070] The obtained solder paste was subjected to viscoelastic properties measurement under the following conditions using a viscoelasticity measuring device, and the loss tangent N0 at a strain of 0.01% and the length of the linear viscoelastic region (the loss tangent is the shear stress value from N0 to 1.1×N0) were calculated. The measurement results of Example 3 of the present invention are shown in FIG. Figure 2 The measurement results of the comparative example are shown in Figure 3 middle.

[0071] Viscoelasticity measurement device: Rheometer manufactured by Anton Paar (model: MCR301)

[0072] Measuring part temperature of viscoelasticity measuring device: 25°C

[0073] The rotation speed (frequency) of the plate of the viscoelasticity measuring device: 1 Hz

[0074] Measuring fixture: PP25

[0075] Gap: 0.3mm

[0076] Sample volume: 0.15mL

[0077] Measurement mode: Strain dispersion

[0078] (Viscosity)

[0079] The viscosity of the obtained solder paste was measured using a viscometer under the following conditions.

[0080] Measuring device: Micro spiral viscometer PCU-02V manufactured by Malcom Co., Ltd.

[0081] Measurement temperature: 25℃±0.11℃

[0082] Measurement speed: 10rpm (shear speed 6 / s)

[0083] Waiting time before measurement: 600s

[0084] Sample volume: 0.2mL

[0085] (Dispensing properties)

[0086] The solder paste obtained was applied to the surface of the Si substrate at 1000 points by the dispensing method using the device shown below, with the coating diameter of 800 μm as the target. The diameter of the applied paste was measured using a one-shot 3D shape measuring machine (VR-5000 manufactured by KEYENCE CORPORATION), and the standard deviation σ of the diameter of the 1000 points was calculated.

[0087] Dispensing machine: ML-606GX (manufactured by MUSASHI ENGINEERING, INC.)

[0088] Robot: SHOTMASTER 300ΩX

[0089] Pellet container: Syringe 5cc (PSY-5E) manufactured by MUSASHI ENGINEERING, INC.

[0090] The case where the paste cannot be ejected during continuous coating of 1000 points and coating of 1000 points cannot be performed is set as "D", the case where the standard deviation σ of the diameters of 1000 points is greater than 20μm is set as "C", the case where the standard deviation σ of the diameters of 1000 points is greater than 10μm and less than 20μm is set as "B", and the case where the standard deviation σ of the diameters of 1000 points is less than 10μm is set as "A".

[0091]

[0092] [Table 2]

[0093]

[0094] In the comparative example, the loss tangent was 0.60 when the strain was 0.01%, a blank weld occurred, and the dispensing property was "D".

[0095] On the other hand, in Examples 1 to 7 of the present invention, the loss tangent at a strain of 0.01% was within the range of 0.1 to 0.5, no solder joints occurred, and the dispensing properties were "C to A".

[0096] In Examples 1 to 4 of the present invention in which the length of the linear viscoelastic region was less than 12 Pa and the viscosity was within the range of 50 Pa·s to 100 Pa·s, the variation in the diameter of the paste after application was suppressed and the dispensing properties were "B to A".

[0097] From the above, it was confirmed that according to the present example, it is possible to provide a solder paste that can be stably supplied even when applied by a dispensing method.

[0098] Industrial Applicability

[0099] According to the present invention, it is possible to provide a solder paste that can be stably supplied even when applied by a dispensing method.

Claims

1. A solder paste comprising metal powder, resin, solvent and thixotropic agent, wherein the solder paste is characterized in that: The loss tangent when the strain is 0.01% is in the range of 0.1 to 0.

5.

2. The solder paste according to claim 1, characterized in that When the loss tangent at a strain of 0.01% is defined as N0, the length of the linear viscoelastic region defined by the range of shear stress corresponding to the strain region where the loss tangent is N0 to 1.1×N0 is less than 12 Pa.

3. The solder paste according to claim 1 or 2, characterized in that: The viscosity measured under the conditions of a temperature of 25° C. and a shear rate of 6 / s is within a range of 50 Pa·s or more and 100 Pa·s or less.

Citation Information

Patent Citations

  • Aluminum casting alloy for intake manifold

    JP1989028339A

  • Optical head for magneto-optical recording carrier

    JP1989059656A

  • Metal paste for soldering and soldering method

    JP2000271782A

  • Solder paste

    JP2023086355A